2018
DOI: 10.1038/s41598-018-32278-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of liquid-liquid phase separation of wheat gliadins

Abstract: During wheat seeds development, storage proteins are synthetized and subsequently form dense protein phases, also called Protein Bodies (PBs). The mechanisms of PBs formation and the supramolecular assembly of storage proteins in PBs remain unclear. In particular, there is an apparent contradiction between the low solubility in water of storage proteins and their high local dynamics in dense PBs. Here, we probe the interplay between short-range attraction and long-range repulsion of a wheat gliadin isolate by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…Our results are in agreement with these findings. By contrast, the phase diagram measured for gliadin by Boire et al (Boire et al, 2018) displays a critical temperature of 12 °C and a protein concentration dependence that is reminiscent of what we observe for samples with Glu ≥ 29 %. This could be explained by the presence of assemblies evidenced by DLS that would pilot the cloud point temperature observed, although the gliadin extract contained only 7.6 % glutenin.…”
Section: Temperature Behaviormentioning
confidence: 46%
See 1 more Smart Citation
“…Our results are in agreement with these findings. By contrast, the phase diagram measured for gliadin by Boire et al (Boire et al, 2018) displays a critical temperature of 12 °C and a protein concentration dependence that is reminiscent of what we observe for samples with Glu ≥ 29 %. This could be explained by the presence of assemblies evidenced by DLS that would pilot the cloud point temperature observed, although the gliadin extract contained only 7.6 % glutenin.…”
Section: Temperature Behaviormentioning
confidence: 46%
“…By definition gliadins are monomeric proteins, but several authors have nevertheless identified the presence of high molar mass proteins (up to 700 000 g/mol) solubilized in this type of solvent (Bietz and Wall, 1980;Schmid, 2016;Shewry et al, 1983). Objects with hydrodynamic radius of about 100 nm co-existing with monomers were observed but disregarded (Boire et al, 2018). Exploiting the low temperature liquid-liquid phase separation of solutions of wheat gluten in ethanol/water 50/50 v/v (Boire et al, 2013), we developed extraction procedures to obtain ethanol/water soluble gluten protein extracts enriched in glutenin.…”
Section: Evidence Of Three Classes Of Objects: Monomers Polymers Andmentioning
confidence: 99%
“…The formation of protein bodies is most probably a result of similar hydrophobic interactions and crosslinking, as described above ( Figure 9 g). An increasing concentration and amount of hydrophobic groups contribute to proteins more prone to self-associating [ 77 , 92 ], which is speculated to be an initial stage of protein body formation for gliadins [ 93 , 94 ]. Folded and aggregated proteins are then transported via different routes to the assembly in PBs at various places in the cell, depending on the stages of grain development.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrenoid 1214 and photobodies 15 , respectively located in chloroplast and nucleus, are best-known plant-specific membrane-less compartments, containing proteins with high disorder profiles. Recent in vitro studies suggest that LLPS could also drive membrane-enclosed organelles formation in wheat seed 16,17 . It has been hypothesized that condensates of wheat storage proteins might play a role as precursor in the formation of their storage organelles, also called protein bodies (PBs).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, all prolamins are known for their low complexity sequence containing rich interspersed repeats which can lead to disordered structures 2426 . Previous works in aqueous buffer/ethanol solution (45/55) (v/v) have shown the ability of whole gliadins extract, comprising a mixture of α, β, γ and ω-gliadins, to self-assemble through LLPS by decreasing temperature 16,27 . It also has been demonstrated the ability of dense gliadins phases to remain in the liquid-like state, even at high protein concentrations (up to 500 g/L) and at low temperatures (from 2 to 20 °C) 16,28 .…”
Section: Introductionmentioning
confidence: 99%